197k views
16 votes
11. rewrite the function in the form y=a (1+r)*

or y=a (1-r) ² then state the growth or decay
rate. y = a (6) t/a

Please help!!

11. rewrite the function in the form y=a (1+r)* or y=a (1-r) ² then state the growth-example-1
User Bryanmac
by
4.7k points

1 Answer

5 votes

Problem 10

The two functions are inverses of each other. Why? Because we can think of f(x) = (x-7)/(-2) as y = (x-7)/(-2).

Swap x and y to get x = (y-7)/(-2). Solving for y leads to y = -2x+7 showing that g(x) = -2x+7 is the inverse of f(x) = (x-7)/(-2). This process can be done in reverse to get the same result.

===================================================

Problem 11

y = a(6)^(t/2)

y = a( 6^(1/2) )^t

y = a(2.4494897)^t

y = a( b )^t

where b = 6^(1/2) = 2.4494897 approximately

Set b equal to 1+r and solve for r

1+r = 2.4494897

r = 2.4494897-1

r = 1.4494897

This rounds to about r = 1.45

The r value is the decimal form of the percentage, which means we move the decimal point over two spots to the right to get 145% approximately

Answers:

The equation is roughly y = a(1 + 1.4494897)^t

The growth rate is approximately 145%

===================================================

Problem 12

You have the correct answer. Nice work.

===================================================

Problem 13

You are very close to the correct answer. However, you're missing the base of the log.

The answer should be
\log_(49)(343) = (3)/(2). So you'll need to write in a small "49" under the log.

The general rule is that exponential equations in the form
b^x = y are equivalent to the log version of
\log_(b)(y) = x. For each equation, b is the base. The idea of logs is to isolate the exponent.

User Eduardo Sousa
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.